PERAN PENDIDIKAN AGAMA DI ERA MODERNISASI SEBAGAI UPAYA PEMBENTUKAN KARAKTER BAIK - M. Ubaidillah Ridwanulloh; Arifah Dwi Wahyu Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
Human life in today's modern era has developed rapidly with the emergence of sophisticated transportation, information, and communication technologies. However, it also has a negative impact, especially on human characters who are currently affected by technology and are becoming a serious problem. Among the negative impacts of technology that appear and affect the human character, especially young people, are on the morality, spirituality, and emotional side. This study aims to describe the role of religious education in the modernization era as an effort to build good character. The research method used is qualitative with the type of case study research. Sources of data obtained from interviews, observation, and documentation. Interviews were conducted with principals, teachers and parents, and guardians. Observations were made in schools during learning, and documentation was obtained on curriculum documents, lesson plans, syllabus, learning photos, and others. The result of the research is that the role of religious education has an important position in character building applied to the students of SDN Segodobancang. Forms of religious education activities both inside and outside the classroom are planting and habituation of being polite to teachers, parents, and others, praying together, praying dhuha, reciting/BTQ, followed by KBM, and praying dhuhur in the congregation. Furthermore, with the COVID-19 pandemic, the habit of planting characters will continue in their respective homes. Teachers always control the implementation of religious activities at home through photos, video calls, contact books, and home visits conducted by homeroom teachers every week. The teacher visits each student's house to see and control the development of student character planting as well as communication with students' parents. This has a positive effect, the community, especially parents and guardians, feels happy and happy with the implementation of the religious education even though the COVID-19 pandemic is ongoing.